Expanding the English medical schools: The politics of knowledge control. (18th April 2016) - Salter, Brian; Filippakou, Ourania; Tapper, Ted
Abstract : Since 1997 there have been two concerted attempts to expand the number of medical school students in England: by increasing the size of existing medical schools, and by creating new medical schools. These initiatives have been a direct result of government policy, although policy implementation was delegated to the state apparatus. They also led to a struggle between higher education interests and the General Medical Council for knowledge control. The aim of this article is to offer an analytical framework for this conflict, and to draw attention to consequent shifts in university governance and the epistemological framing of higher education.